Outcomes of regional anesthesia in cancer patients. Issue 5 (October 2018) - Cata, Juan P.
Abstract : Purpose of review: To summarize the current evidence on the impact of regional anesthesia or analgesia on cancer recurrence. Recent findings: Preclinical investigations suggest that regional anesthesia could have a positive impact on reducing cancer growth and progression. Regional anesthesia is also associated with better immunological and stress-related outcomes in patients undergoing major oncological surgery. Most recent retrospective studies do not show any benefit of regional anesthesia or analgesia on cancer recurrence or recurrence-free survival. Summary: The available clinical evidence does not support the use of any anesthesia technique to improve the cancer-related survival after major oncological surgery. The results from four randomized controlled trials will shed light on this critical topic in perioperative medicine.